Sunrise ebook - Warren, Susan May (Sky King Ranch, 2022)
A decade after leaving his family's bush pilot operation to become a Pararescue Jumper, Dodge Kingston is back home in Alaska. He hadn't counted on meeting up again with Echo, a girl with a spirit as free as the sky. When she goes missing, he hopes all her skills will keep her safe until he can reach her—and that she'll accept his help when he does.